Corporate Social Responsibility in the restaurant and fast food industry: a study of communication on healthy eating through social networks - Martínez-Sala,Alba-María (2021)
The communication of Corporate Social Responsibility (CSR) of a sample of eight restaurant and fast food companies is analyzed. An exploratory and descriptive method, based on the content analysis technique, is used to analyze the formal and informal CSR communication channels used to promote healthy eating on their respective websites and Twitter profiles. This study is complemented by a survey (n = 383) applied to a sample of young Spaniards to investigate their interest in healthy eating information, their assessment of CSR actions carried out in this area as well as the communication channels used for this purpose. The results confirm that the CSR policies of the companies include actions aimed at guaranteeing and promoting healthy eating. It is concluded about the convenience of using their own social networks and influencers to encourage healthy eating habits more effectively in their publics.